Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(15^4-12x^3+9x^2\)
b,\(-15x^3y^2+25x^2y^2-5xy^3\)
c, \(5x^3-19x^2+12x\)
d,
x3+xy2+5x2y−9x2y−3y3−15xy2=3x3−3y3−14xy2−4x2y
\(a,=15x^4-12x^3+9x^2\\ b,=-15x^3y^2+25x^2y^2-5xy^3\\ c,=5x^3-15x^2-4x^2+12x=5x^3-19x^2+12x\\ d,=3x^3+xy^2+5x^2y-9x^2y-3y^3-15xy^2=3x^3-14xy^2-4x^2y-3y^3\)
\(a,=15x^4-12x^3+9x^2\\ b,=-15x^3y^2+25x^2y^2-5xy^3\\ c,=5x^3-19x^2+12x\\ d,=3x^3+xy^2+5x^2y-9x^2y-3y^3-15xy^2\\ =3x^3-3y^3-14xy^2-4x^2y\)
a) \(2xy\left(3x^2-5xy+4y^2\right)=6x^3y-10x^2y^2+8xy^3\)
b) \(\left(x-3\right)^2+\left(x+5\right)\left(5-x\right)=x^2-6x+9+25-x^2=34-6x\)
a: \(2xy\left(3x^2-5xy+4y^2\right)=6x^3y-10x^2y^2+8xy^3\)
b: \(\left(x-3\right)^2+\left(x+5\right)\left(5-x\right)\)
\(=x^2-6x+9+25-x^2\)
=-6x+34
a:\(2x^2y\left(3x^2-5xy+4y^2\right)-6x^4y-10x^3y^2+8x^2y^3\)
b: \(\left(x^2-9\right)^2-\left(x+3\right)\left(x-3\right)\left(x^2+9\right)\)
\(=x^4-18x^2+81-\left(x^4-81\right)\)
\(=-18x^2+162\)
Bài 1:
\(a,=15x^4-12x^3+9x^2\\ b,=-15x^3y^2+25x^2y^2-5xy^3\\ c,=5x^3-15x^2-4x^2+12x=5x^3-19x^2+12x\\ d,=3x^3-9x^2y+xy^2-3y^3+5x^2y-15xy^2=3x^3-3y^3-4x^2y-14xy^2\)
Bài 2:
\(a,=x^2+4x-21-x^2-4x+5=-16\\ b,=x^2+16x+64-2x^2-12x+32+x^2-4x+4=100\\ c,=x^4-16x^2-x^4+1=1-16x^2\\ d,=x^3+1-x^3+1=2\)
2x^2-5xy-3y^2
= 2^x + xy - 6xy - 3y^2
= x(2x + y) - 3y(2x + y)
= (2x + y)(x - 3y)
\(=3x^3+4xy^2-5x^2y-9x^2y-12y^3+15xy^2\)